STRATEGI PENGEMBANGAN OBJEK WISATA PEMANDIAN LUBUK MATA KUCING KOTA PADANG PANJANG - Yolveri Yolveri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The city government of Padang Panjang has developed several tourism objects, one of which is the Lubuk Mata Kucing bath because there are still not many tourism who have not seen the object, due to the location which is on the outskirts of the city and road directions to tourism objects are still lacking, then indirectly affect the level of tourism visits. The Lubuk Mata Kucing bath is indeed very minimal promotion and exposes tourism objects to the crowd, so you do not see this beautiful tourism attraction, in addition to the lack of promotion in the facilities section. The Indonesian government has tried to make Indonesia one of the tourism destinations for tourism and make Indonesia the main destination for tourism, tourism who visit many tourism objects in Indonesia automatically improve the economy of local residents and foreign exchange, as is being done by the Padang government. Panjang In making improvements to one of the tourism objects, namely the Lubuk Mata Kucing bath, to be a better tourism attraction. The development of the world of tourism and increased competition in the Tourism Industry of the Padang Panjang City Government, especially the Tourism Office, should carry out various development strategies so that tourism in the City of Padang Panjang is not left behind as one of the Lubuk Mata Kucing bathing objects that can develop and attract tourism to visit. The Municipal Government of Padang Panjang cooperates with other parties that are expected to increase the level of tourist visits.